Choosing the best molecular precursor to prepare Li4Ti5O12 by the sol–gel method using 1H NMR: evidence of [Ti3(OEt)13]− in solution. Issue 35 (15th August 2016) - García-Herbosa, Gabriel; Aparicio, Mario; Mosa, Jadra; Cuevas, José V.; Torroba, Tomás
Abstract : 1 H NMR spectroscopy can be used to choose the best precursor to prepare the lithium ionic conductor Li4 Ti5 O12 by the sol–gel method. Abstract : 1 H NMR spectroscopy at 400 MHz in toluene-d8 of evaporated mixtures of lithium ethoxide and titanium(iv ) isopropoxide in ethanol, used to prepare the spinel Li4 Ti5 O12 by the sol–gel method, may help clarify why the atomic ratio 5Li : 5Ti and not 4Li : 5Ti is the right choice to obtain the pure phase when performing hydrolysis at room temperature. The mixtures x LiOEt/ y Ti(OPr i )4 in ethanol undergo alcohol exchange at room temperature, and the evaporated residues contain double lithium–titanium ethoxide [LiTi3 (OEt)13 ] rather than simple mixtures of single metal alkoxides; this is of great relevance to truly understanding the chemistry and structural changes in the sol–gel process. Detailed inspection of the 1 H and 13 C VT NMR spectra of mixtures with different Li/Ti atomic ratios unequivocally shows the formation of [LiTi3 (OEt)13 ] in a solution at low temperature. The methylene signals of free lithium ethoxide and Li[Ti3 (OEt)13 ] coalesce at 20 °C when the atomic ratio is 5 : 5; however, the same coalescence is only observed above 60 °C when the atomic ratio is 4 : 5. We suggest that the highest chemical equivalence observed by 1 H NMR spectroscopy achieved through chemical exchange of ethoxide groups involves the highest microscopic structural homogeneity of the sol precursor and will lead to the best gel after hydrolysis. Variable temperature 1 H NMR spectra at 400 MHz of variable molar ratios of LiOEt/Ti(OPr i )4 are discussed to understand the structural features of the sol precursor. While the precursor with the atomic ratio 5Li : 5Ti shows no signal of free LiOEt at 20 °C, both 4Li : 5Ti and 7Li : 5Ti show free LiOEt at 20 °C in their 1 H NMR spectra, indicating that the molar ratio 5Li : 5Ti gives the maximum rate of chemical exchange. DFT calculations have been performed to support the structure of the anion [Ti3 (OEt)13 ] − at room temperature.